Mechanisms influencing particle depletion in and around mussel farms in different environments. (March 2021) - Taylor, Daniel; Larsen, Janus; Buer, Anna-Lucia; Friedland, Rene; Holbach, Andreas; Petersen, Jens Kjerulf; Nielsen, Pernille; Ritzenhofen, Lukas; Saurel, Camille; Maar, Marie
Highlights: An updated model demonstrates particle depletion under different conditions. Depletion is driven by interactions of environmental variables. Spatial statistical methods can describe patterns of depletion. Farm-scale mussel growth is modulated by osmoregulatory expenditure and food flux. Abstract: Through the mechanisms of particle immobilization and subsequent depletion of particles, mussel cultivation has a direct effect on chlorophyll-a concentrations and Secchi depth; both of which are primary indicators of marine ecological status and metrics for water quality management. As such, mussel cultivation has been proposed as a measure to mitigate the effects of coastal eutrophication. However, the extent to which this ecosystem service, and relatedly, biomass accumulation, are affected by ambient environmental conditions involves complex interactions. To explore the interacting mechanisms underpinning depletion dynamics under various biophysical conditions along the salinity gradient in the Baltic Sea, we used an updated Dynamic Energy Budget (DEB) model with field data from the western Baltic Sea, accommodating osmotic stress. We use the DEB model to drive a 3D farm-scale model within a novel precompiled hydrodynamic framework (FlexSem) to evaluate the effects of different environmental conditions and farm configuration on the intensity and extent of the chlorophyll-a depletion signal. We also report on extensive in situ monitoring of chlorophyll-a and Secchi depth within and around mussel farms, from several cultivation areas from around the western Baltic Sea to evaluate site-specific characteristics of depletion. Monitoring reflected the high degree of spatio-temporal variability in the quantification of this ecosystem service; with relative differences in chlorophyll-a from −14 to 69% and Secchi depth from 0 to 75%. We find that the extensive in situ measurements in different environmental conditions can be represented by the integrated farm model in terms of mussel biomass accumulation and depletion, providing insight on the interactions of current velocity, farm orientation to predominant current direction, ambient chlorophyll-a concentrations, and total biomass loads on the intensity and spatial extent of the depletion signal. Furthermore, the model has been calibrated to cover a variety of environmental contexts and permits fine-resolution simulation of multiple environmental interactions on mussel energetics, which can be used to evaluate potentials for optimizing mussel mitigation culture and the associated ecosystem services of phytoplankton depletion under local conditions without extensive recalibration from field growth data. The general interactions exhibited here and model will be useful for evaluating depletion and planning the establishment of mitigation farms in regions where national environmental monitoring programs can provide basic data. This can also reduce the need for extensive and costly in situ monitoring programs.